A novel electrolyte additive for improving the interfacial stability of LiMn2O4 cathode lithium-ion batteries at elevated temperature. Issue 68 (19th November 2018) - Huang, T.; Zheng, X.; Fang, G.; Pan, Y.; Wang, W.; Wu, M.
Abstract : Methanesulfonic acid 2, 2, 3, 3-tetrafluoropropyl (TFPMS) is newly explored as a protection additive to improve the interfacial stability of LiMn2 O4 cathode/electrolyte at an elevated temperature. Abstract : Methanesulfonic acid 2, 2, 3, 3-tetrafluoropropyl (TFPMS) is newly explored as a protection additive to improve the interfacial stability of LiMn2 O4 cathode/electrolyte at an elevated temperature. At 1C rate, the addition of 0.5 vol% TFPMS improves the capacity retention of an LiMn2 O4 /Li cell from 56.9% to 72.9% after 200 cycles at 55 °C. Electrochemical impedance spectroscopy (EIS) and transmission electron microscopy (TEM) results suggest that the electrolyte with 0.5 vol% TFPMS forms a thinner and less resistive interface. X-ray photoelectron spectroscopy (XPS) analysis reveals that the addition of TFPMS restrains the formation of LiF and Li2 CO3 . Moreover, X-ray diffraction (XRD) and inductively coupled plasma (ICP) analysis confirms the effectiveness of TFPMS-enhanced structural stability of LiMn2 O4.